A new species of insular Rock Gecko (Genus Cnemaspis Strauch, 1887) from the Bidong Archipelago, Terengganu, Peninsular Malaysia - Grismer, L. Lee; Jr., Perry L. Wood; Ahmad, Amirrudin B.; Sumarli, Alexandra S.-I.; Vazquez, Jessika J.; Ismail, Lukman H. B.; Nance, Ronald; Mohd-Amin, Muhammad Afif B.; Othman, Mohamad N. A. B.; Rizaijessika, Syed A.; Kuss, Maria; Murdoch, Matthew; et al. (Zootaxa, 2014)
A new insular species Cnemaspis bidongensis sp. nov. (Squamata: Gekkonidae), is described from Pulau Bidong, Terengganu, Peninsular Malaysia and bears a unique suite of morphological and color pattern characters that differentiate it from all other congeners. Cnemaspis bidongensis sp. nov. is the sister species to C. kendallii (Gray) and represents the fifth insular endemic species of Cnemaspis on archipelagos along the east coast of Peninsular Malaysia. This species survived massive deforestation of the small island of Bidong (260 ha) from the mid 1970s to the early 1990s when the island served as a Vietnamese refugee camp and harbored as many as 40,000 people at one time. We hypothesize that this species’ generalized lifestyle contributed to its survival, allowing it to seek refuge in rocky microhabitats.